Post-Operative Complications of Illeal Perforation: Experienced of 100 Patients in Bangladesh - Begum, Mahbuba; Majid, MA; Joarder, Ruhul Hasan; Rahman, Mostafizur; Debnath, Bidyut Chandra; Mohammad, Abu Sayeed; Begum, Wahida; Mohammad, Din (Journal of Current and Advance Medical Research, 2016)
Background: Ileal perforation is a serious surgical emergency. Objective: The objective of the present study was to see the post-operative complications of ileal perforation patients. Methodology: This cross sectional study was conducted in the Department of Surgery at Dhaka Medical College Hospital, Dhaka from September 2000 to December 2002 for period of 2 years and 3 months. All the patients presented with ileal perforation at any age with both sexes were included in this study. Patients were selected consecutively and the patients who showed ileal perforation at laparotomy were included in this study. A standard protocol was filled up for every patient. Preoperative diagnosis was based on detailed history, complete physical examinations supported by plain x-ray abdomen in erect posture including both domes of diaphragm. After immediate resuscitation surgical treatment was undertaken as soon as possible following admission in all cases. Surgical procedures included simple repair, wedge resection and repair, resection and anastomosis, right hemi colectomy and temporary ileostomy. Histopathological examination of tissues from the margin of perforation and mesenteric lymph nodes were carried out in almost all cases. Result: Out of 100 patients complications were observed in 53 patients. Thus, incidence of complication was 53%. In 47 patients postoperative period was uneventful. Most of the complications were observed around 3rd to 5th post-operative day. Wound infection was the most common complication and noted in 4th to 7th postoperative day. Respiratory complications were also common and mostly observed on 2"dpostoperative day. All these patients presented with loose motion and lower abdominal pain on 3rd postoperative day. Faecal fistula developed on 3rd to 5th postoperative day in 3 cases resulting from disruption of simple repair in 2 cases and anastomotic leakage in 1 case who later died complicated by septicemia and multi-organ failure. Conclusion: Wound infection is the most common post-operative complication followed by septicemia and respiratory complication. Journal of Current and Advance Medical Research 2016;3(1):2-5